Education of Clean and Healthy Living Behaviors for Students of UPT SPF SD Negeri 101900 Lubuk Pakam - Pitriani, Pitriani; Hayati, Kardina; kesumawardani, Nadya Ulfa; Sitepu, Abdi Lestari (JURNAL PENGMAS KESTRA (JPK), 2024)
Clean and Healthy Living Behavior (PHBS) is behavior that is implemented in daily life based on initiatives originating from learning outcomes so that it can change individuals or groups so that they can play an active role in their health in society. School-age children are children who are in childhood, which is clearly in contrast to adulthood. During childhood, there are generally many health problems that are critical in determining the quality of a child's health in the future. Community service is the key to efforts to spread knowledge about PHBS. This community service was carried out for elementary school students in grades 4, 5, and 6 at SD Negeri 101900 Lubuk Pakam, as many as 100 people. This activity will play a role in raising students' awareness of implementing PHBS behavior and infectious disease prevention behavior at school. This activity is held through counseling, and public campaigns, where PkM will be able to increase understanding about washing hands before and after carrying out activities, brushing teeth, not littering, and not snacking carelessly. Evaluation of this activity is carried out through review activities by asking questions to elementary school students. The results of this PkM show that there has been a significant increase in awareness, knowledge, and prevention efforts in implementing PHBS at SD Negeri 101900 Lubuk Pakam. It is hoped that students will remain consistent in implementing PHBS in their daily activities.